A while ago, I started to look at expressions of the following form: $$ S_p:=\sum_{n=1}^\infty \frac1n - \frac1{n+1/p}, $$ where $p$ is prime, because otherwise things get too complicated for me at the moment. What I found so far is the following: $$ S_p= p -\log(2p) - \frac12 \pi \cot\left(\frac\pi p\right) + T_p, $$ where $T_p$ contains $\frac{p-1}2$ terms $t_{p,k}$ of the form: \begin{cases} \pm 2 \sin\left(\frac{k\pi}{2p}\right) \log\left(\sin\left(\frac{k\pi}{2p}\right)\right) \\ \pm 2 \cos\left(\frac{k\pi}{2p}\right) \log\left(\sin\left(\frac{k\pi}{2p}\right)\right)\\ \pm 2 \sin\left(\frac{k\pi}{2p}\right) \log\left(\cos\left(\frac{k\pi}{2p}\right)\right) \\ \pm 2 \cos\left(\frac{k\pi}{2p}\right) \log\left(\cos\left(\frac{k\pi}{2p}\right)\right) \end{cases}

An example can be found here.

How does the closed form for $\sum_{n=1}^\infty \frac1n - \frac1{a+n}$ look like? (EDIT: where $a=1/p$)

  • $\begingroup$ Are you looking for this formula? $$\psi\left(\frac{m}{k}\right) = -\gamma - \log(2k) - \frac{\pi}{2}\cot\left(\frac{m\pi}{k}\right) + 2\sum_{n=1}^{\lfloor\frac{k-1}{2}\rfloor} \cos\left(\frac{2\pi nm}{k}\right)\log\left(\sin\left(\frac{n\pi}{k}\right)\right)$$ where $m$ and $k\;(m < k)$ are positive integers. (Note: I've no idea how to prove this) $\endgroup$ – achille hui Jul 12 '14 at 9:11
  • $\begingroup$ @achillehui looks promising... $\endgroup$ – draks ... Jul 12 '14 at 10:04

First, for any $z \in \mathbb{C}$ with $|z| < 1$, we have following expansion

$$-\log(1-z) = \sum_{n=1}^\infty \frac{z^n}{n}$$

Let $\displaystyle\;\omega = e^{\frac{i2\pi}{p}}\;$ be the primitive $p$-root of unity, we know for any integer $n$,

$$\frac{1}{p}\sum_{\ell=0}^{p-1} (\omega^\ell)^n = \delta_p(n) \stackrel{def}{=} \begin{cases}1,& n \equiv 0\pmod p\\0,& \text{otherwise}\end{cases}$$ This implies for any integer $k \in \{\;1,2,\ldots,p\;\}$, we have

$$-\frac{1}{p}\sum_{\ell=0}^{p-1}\omega^{-k\ell}\log(1-z\omega^\ell) = \frac{1}{p}\sum_{\ell=0}^{p-1}\sum_{n=1}^\infty \frac{z^n}{n}( \omega^\ell )^{n-k} = \sum_{n=1}^\infty \delta_p(n-k)\frac{z^n}{n} = \frac{1}{p}\sum_{n=0}^\infty \frac{z^{np+k}}{n+\frac{k}{p}} $$

This leads to $$\sum_{n=0}^\infty\left(\frac{1}{n+1} - \frac{1}{n+\frac{k}{p}}\right)z^{np} = - \sum_{\ell=0}^{p-1}\left(z^{-p} - z^{-k}\omega^{-k\ell}\right)\log(1-z\omega^\ell) \tag{*1}$$ Since the sequences $\displaystyle\;\frac{1}{n+1} - \frac{1}{n+\frac{k}{p}} \sim O\left(\frac{1}{n^2}\right)\;$, the series on the LHS converges absolutely as $z \to 1^{-}$. The RHS is a finite sum, the only term that may cause trouble is the term for $\ell = 0$. It is clear the logarithm singularity from the $\log(1-z)$ get killed by the $z^{-p} - z^{-k}$ factor as $z \to 1^{-}$. This allow us to take the limit $z \to 1^{-}$ in $(*1)$ and get $$\mathcal{S}_{k/p} \stackrel{def}{=} \sum_{n=1}^\infty\left(\frac{1}{n} - \frac{1}{n+\frac{k}{p}}\right) = \frac{p}{k} + \sum_{n=0}^\infty\left(\frac{1}{n+1} - \frac{1}{n+\frac{k}{p}}\right)\\ = \frac{p}{k} - \sum_{\ell=1}^{p-1}\left(1 - \omega^{-kl}\right)\log(1-\omega^\ell) $$ Using the identities

$$\sum_{\ell=1}^{p-1}\log(1-\omega^\ell) = \log p \quad\text{ and }\quad \sum_{\ell=1}^{p-1}\omega^\ell = -1$$ The sum reduces to $$\begin{align} &\frac{p}{k} - \log(2p) + \sum_{l=1}^{p-1}\omega^{-k\ell}\log\left(\frac{1-\omega^\ell}{2}\right)\\ = & \frac{p}{k} - \log(2p) + \sum_{l=1}^{p-1} \left( \cos\left(\frac{2\pi k\ell}{p}\right) - i\sin\left(\frac{2\pi k\ell}{p}\right) \right)\left(\log\sin\left(\frac{\ell\pi}{p}\right) + i\pi\left(\frac{\ell}{p}-\frac12\right)\right) \end{align} $$ Using another set of trigonometric identities $$\sum_{\ell=1}^{p-1}\frac{\ell}{p}\sin\left(\frac{2\pi k\ell}{p}\right) = -\frac12\cot\left(\frac{k\pi}{p}\right) \quad\text{ and }\quad \sum_{\ell=1}^{p-1}\sin\left(\frac{2\pi k\ell}{p}\right) = 0 $$ We finally get $$ \bbox[4pt,border:1px solid blue]{ \mathcal{S}_{k/p} = \frac{p}{k} - \log(2p) -\frac{\pi}{2}\cot\left(\frac{k\pi}{p}\right) + \sum_{l=1}^{p-1} \cos\left(\frac{2\pi k\ell}{p}\right) \log\sin\left(\frac{\ell\pi}{p}\right) } \tag{*2} $$

On the wiki page of digamma function, there is a formula for digamma function at $\frac{k}{p}$.

$$\psi\left(\frac{k}{p}\right) = -\gamma - \log(2p) - \frac{\pi}{2}\cot\left(\frac{k\pi}{p}\right) + 2\sum_{\ell=1}^{\lfloor\frac{p-1}{2}\rfloor} \cos\left(\frac{2\pi k\ell}{p}\right)\log\sin\left(\frac{\ell\pi}{p}\right)$$

Compare this with what we have in $(*2)$, we can simplify our sum as

$$\mathcal{S}_{k/p} = \frac{p}{k}+\psi\left(\frac{k}{p}\right) + \gamma = \psi\left(\frac{k}{p}+1\right) + \gamma$$

Replace $\frac{k}{p}$ by $a$, this matches the result derived in another answer.

  • $\begingroup$ A creative application of series multisection. (+1) $\endgroup$ – Markus Scheuer Mar 12 at 5:56

$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$ $\ds{\mbox{How does the closed form for}\ \sum_{n = 1}^{\infty}\pars{{1 \over n} - {1 \over a + n}}\ \mbox{look like ?}}$

\begin{align} \!\!\sum_{n = 1}^{\infty}\pars{{1 \over n}\! - \!{1 \over a + n}} &\!=a\sum_{n = 1}^{\infty}{1 \over n\pars{a + n}} \!=a\sum_{n = 0}^{\infty}{1 \over \pars{n + 1 + a}\pars{n + 1}} =\!a\,{\Psi\pars{1 + a} \!-\! \Psi\pars{1} \over \pars{1 + a} - 1} \end{align} where $\ds{\Psi\pars{z}}$ is the Digamma Function $\ds{\bf\mbox{6.3.1}}$ and we used identity $\ds{\bf\mbox{6.3.16}}$.

$$\color{#66f}{\large% \sum_{n = 1}^{\infty}\pars{{1 \over n} - {1 \over a + n}} =\Psi\pars{1 + a} + \gamma} = {\rm H}_{a} $$

$\ds{\gamma = -\Psi\pars{1}}$ is the Euler-Mascheroni Constant $\ds{\bf\mbox{6.1.3}}$. $\quad\ds{\gamma \approx 0.5772156649\ldots\quad}$ $\ds{{\rm H}_{a}}$ is a generalized Harmonic Number.

  • $\begingroup$ Looks good, but not what I was looking for. Can express it that in the terms given in the question? $\endgroup$ – draks ... Jul 12 '14 at 5:44
  • $\begingroup$ @draks... There isn't way to escape from the ${\large \bf{\tt\mbox{Harmonic Number}}}$. It's even suggested by the question. $\endgroup$ – Felix Marin Jul 12 '14 at 8:20
  • $\begingroup$ So you say there is no rule to generate the $t_{p,k}$ terms, that show up in my example? Unbelievable... $\endgroup$ – draks ... Jul 12 '14 at 8:52
  • $\begingroup$ @draks... I'll think about it. Now, it's too late. Tomorrow I can make some comment about. Thanks. $\endgroup$ – Felix Marin Jul 12 '14 at 9:08
  • $\begingroup$ @draks... $\tt\color{#66f}{\mbox{@achille hui}}$ already pointed out the connection between my answer and your expected result. Thanks. $\endgroup$ – Felix Marin Jul 14 '14 at 20:21

Write your expression as the limit at $x \to 1$ of $$\sum_{n = 1}^{\infty} \frac{p x^{pn}}{pn} - \frac{p x^{pn+1}}{pn+1}.$$

If we differentiate this power series, we get $$\sum_{n = 1}^{\infty} p x^{pn - 1} - p x^{pn} = p x^{p-1} \frac{1-x}{1 - x^p}. $$ Integrating this (say via a partial fraction decomposition) and then choosing the constant of integration so that you get zero when $x = 0$ gives a formula for the original power series. Now putting $x = 1$ gives the value you want.

E.g. if $p = 2$, we have
$$2 x \frac{1}{1+x} = 2 - \dfrac{2}{1+x},$$ whose desired integral is $$2x - 2\log (1+x),$$ and so the value of the sum in this case is $2-2\log 2.$

E.g. if $p = 3$, we have $$3 \frac{x^2}{1+x+x^2} = 3 - 3\frac{1+x}{1+x+x^2} = 3 - \frac{3}{2} \frac{2x+1}{1+x+x^2} - \frac{3}{2}\frac{1}{3/4+ (x+1/2)^2},$$ whose desired integral is $$3 x - \frac{3}{2}\log(1+x+x^2) - {\sqrt{3}}\arctan\bigl(\frac{2x+1}{\sqrt{3}}\bigr)+\sqrt{3} \frac{\pi}{6},$$ and so the value of the sum in this case is $$3 - \frac{3\log 3}{2} - \frac{\sqrt{3} \pi}{6}.$$

I didn't try to find the general formula here. One part of mathematics where it is worked out is the theory of special values (at $s = 1$) of Dirichlet $L$-series.

[Added: it seems that between when I began writing this yesterday, and when I finally got a chance to finish and post it now, other answers with related derivations have appeared. Oh well.]

  • $\begingroup$ I appreciate your approach. Thanks +1... $\endgroup$ – draks ... Jul 12 '14 at 21:25

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.